(untitled) (Communications in Computational Physics, 2008)
Two-component submonolayer growth on triangular lattice is qualitatively studied by kinetic Monte Carlo techniques. The hopping barrier governing surface diffusion of the atoms is estimated using pair interaction potentials. Several degrees of freedoms enhancing the surface diffusion of atoms are also introduced. The main advantages of the presented technique are the reduced number of free parameters and the clear diffusion activated mechanism for the segregation of different types of atoms. The potential of this method is exemplified by reproducing (i) phase-boundary creation and dynamics related to vacancies and stacking faults; (ii) a special co-deposition and segregation process where the segregated atoms of the second component surround the islands formed by the first type of atoms.